Privacy Preserving Technique for Mitigating Anonymity Attack in Pervasive Social Networking Applications - Ayuni binti Adnan, Nur’; Mahinderjit Singh, Manmeet; Jantan, Aman (International Journal of Engineering and Technology, 2018)
Pervasive Social Networking (PSN) applications become more popular in the last few years. The uses of PSN applications through mobile devices such as smartphones, tablets will lead to the security and privacy issues. This is because users tend to share their personal information with the third party organizations such as applications in mobile devices. Due to the development of social network, the security and privacy need to be improved as well as others to make sure that all the user’s information is protected securely in social network (SN). In this study, we will focus more on the privacy issues on how to preserve the privacy of user’s data from being known by the third party. The dataset of PSN application will be tested using data mining tool, which is Weka, in order to identify the optimal technique and classifier that can be applied to conceal the information. Then, a new enhanced base learner will be proposed, which is masking technique algorithms will be implemented into the dataset of PSN application at the end of this research.